Peran Guru Sebagai Pembimbing Akhlak dan Ilmu dalam Islam : Membangun Generasi Berkarakter - Anggi Pradana; Sutarto Sutarto (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2025)
This study aims to analyze the role of teachers in guiding morals and knowledge in Islamic education, and explore how the balance between these two aspects can be applied in the context of modern education. This study uses a literature study method by reviewing various library sources related to Islamic education, the role of teachers, and the integration of morals in learning. Data were obtained from books, journal articles, and other sources relevant to the research topic. The results of the study indicate that teachers have a very important role in guiding students' morals and knowledge. Islamic education teaches the importance of balance between these two aspects, where teachers not only teach knowledge, but also shape students' characters according to Islamic values. The main challenge faced is how to integrate morals with knowledge in the increasingly modern and developing world of education. Teachers are expected to be able to carry out dual tasks in educating morals and knowledge to students. Therefore, an effective strategy in combining these two elements is very important to produce a generation with noble morals and knowledge. This study provides important insights into the strategic role of teachers in creating a balance between knowledge and morals in Islamic education.